Prevalence of Chronic Bronchitis in the Northwest of Iran: Results of the Pilot Phase of the Azar Cohort Study - Delara Laghousi; Mahasti Alizadeh; Nayyereh Aminisani; Javid Sadeghi; Mohammad Asghari Jafarabadi (Shahrekord University of Medical Sciences, 2018)
Background and aims: Although chronic bronchitis is markedly under-diagnosed in the general population, it has a significant impact on the health status and the well-being of patients as well as healthcare resource consumption. This study aimed to determine the prevalence of chronic bronchitis and its correlates in the northwest of Iran. Methods: In 2014, all residents aged 35 and over in Khameneh city, East Azerbaijan, were invited to participate in the pilot phase of the Azar cohort study. The respiratory symptoms questionnaires were filled out by two trained general practitioners. Participants with a cough and phlegm on most days during at least three successive months in the previous two years were classified as chronic bronchitis group. Chi-square test was used to compare the chronic bronchitis and smoking status between males and females. Results: A total of 1036 participants were interviewed, 1006 of whom had completed a respiratory questionnaire, from them 544 (54.1%) were females, and 462 (45.9%) were males. The mean age was 52.5 ± 10.5 years. The prevalence of smoking was 16.2%. According to the chronic bronchitis definition, 24 (2.4%) subjects were classified with chronic bronchitis, and the prevalence was higher in the males (4.1%) than that in the females (0.9%). The prevalence was higher among the active smokers and ex-smokers compared to non- smokers (8.6% and 4.1% vs. 0.8%). The prevalence of cigarette smoking was 16.2% and it was higher in the males than that in the females (33.5% vs. 1.5%). Conclusion: the prevalence of chronic bronchitis in the population of the region under study was relatively low in comparison to the other parts of Iran and its prevalence was higher in the males than that in the females.